Dosimetry advantages of intraoperatively built custom-linked seeds compared with loose seeds in permanent prostate brachytherapy - Inada, Masahiro; Yokokawa, Masaki; Minami, Takafumi; Nakamatsu, Kiyoshi; Nishimura, Yasumasa (Journal of Contemporary Brachytherapy, 2017)
Abstract Purpose: The aim of this study was to compare the implant quality between intraoperatively built custom-linked seeds (IBCL) and loose seeds (LS) retrospectively. Material and methods: This study included 74 prostate cancer patients who were treated with permanent prostate brachytherapy (PPB) using IBCL (n = 37) or LS (n = 37) between July 2014 and June 2016. Dose-volume histogram (DVH) parameters, seed migration, and operation time were compared between the IBCL and LS groups. In addition to the standard target volume of the whole prostate gland, DVH parameters for prostate plus a 3 mm margin (CTV) were evaluated. Results : In intraoperative planning, prostate V150 was lower (54.8% vs. 59.6%, p = 0.027), and CTV V100 (88.1% vs. 85.6%, p = 0.019) and D90 (98.5% vs. 92.6%, p = 0.0033) were higher in the IBCL group compared with in the LS group. In post-implant dosimetry, prostate V100 (96.9% vs. 95.2%, p = 0.020), CTV V100 (85.6% vs. 81.7%, p = 0.046), and CTV D90 (94.2% vs. 86.5%, p < 0.001) were higher, and prostate V150 (57.1% vs. 64.5%, p = 0.0051) and CTV V150 (31.5% vs. 35.7%, p = 0.046) were lower in the IBCL group compared with in the LS group. Regarding DVH changes between intraoperative planning and post-implant dosimetry, the decrease in prostate D90 was significantly lower in the IBCL group than in the LS group (–1.16% vs. –4.17%, p < 0.001). For the IBCL group, the operation time was slightly but significantly longer than that for the LS group (50.5 minutes vs. 43.7 minutes, p = 0.011). However, the seed migration rate was significantly lower in the IBCL group than in the LS group (5% vs. 41%, p < 0.001). Conclusions : Intraoperatively built custom-linked is more advantageous than LS in terms of dosimetric parameters and migration.